Valorization of residual Empty Palm Fruit Bunch Fibers (EPFBF) by microfluidization: Production of nanofibrillated cellulose and EPFBF nanopaper - Ferrer, Ana; Filpponen, Ilari; Rodríguez, Alejandro; Laine, Janne; Rojas, Orlando J. (Bioresource technology, 2012)
► Empty Palm Fruit Bunch Fibers (EPFBF) were subject to sulfur-free chemical treatments. ► Microfluidization of EPFBF yields nanofibrils comparable to those from wood fibers. ► Nanopaper with excellent properties was manufactured from nanofibrillar EPFBF. ► Valorization of EPFBF is attractive due its higher yields and lower costs. Different cellulose pulps were produced from sulfur-free chemical treatments of Empty Palm Fruit Bunch Fibers (EPFBF), a by-product from palm oil processing. The pulps were microfluidized for deconstruction into nanofibrillated cellulose (NFC) and nanopaper was manufactured by using an overpressure device. The morphological and structural features of the obtained NFCs were characterized via atomic force and scanning electron microscopies. The physical properties as well as the interactions with water of sheets from three different pulps were compared with those of nanopaper obtained from the corresponding NFC. Distinctive chemical and morphological characteristics and ensuing nanopaper properties were generated by the EPFBF fibers. The NFC grades obtained compared favorably with associated materials typically produced from bleached wood fibers. Lower water absorption, higher tensile strengths (107–137MPa) and elastic modulus (12–18GPa) were measured, which opens the possibility for valorization of such widely available bioresource.